(untitled) (Pedagogy of Higher and Secondary Education, 1999)
Article is dedicated to the questions of the practical work with the music on the lessons of painting art in the beginning forms of the school. She is about the problem of the development of emotional side in the childish creativity and the role o f music, which is foundation of the formation of emotions and creating of art active the atmosphere. This experimental method was approbated in one of schools of the town of Kryvyi Rih and he is introduced our in this article. In the text, there’s thematic planning for the first form of the school in the learning of the founds of painting art, which is given for the practical work to the teachers of the beginning school.